Understanding Plagiarism: A Guide for Lecturers - UiTM, Institute of Quality & Knowledge Advancement (InQKA) (Institute of Quality & Knowledge Advancement, UiTM, 2012)
Plagiarism has long been a problem but has grown explosively with the advent of ICT and the Internet. In universities, plagiarism seems to be prevalent and pernicious, putting academic integrity under threat. It indicates students' failure to observe good writing habits and ethics. Having an academic integrity policy is not enough. It must be communicated to all students. The university - that is you, me and all who inhabit the teaching and learning space - must accept, adhere to, articulate and apply plagiarism policies consistently and seriously. If we do not stand up and address this, we would have failed future generations of graduates in ethics, professionalism and values. In the fight against this growing problem, lecturers are the most important group in shaping students' behaviour and attitudes. Lecturers can limit the scope for plagiarism in various ways; for example: design assessments that require reflection and thinking; lower the motivation to plagiarise by being reasonable with assessments; increase the risk of detection by using ICT to detect and deter culprits; and raise the costs of plagiarism by taking take stern action in cases of intentional plagiarism.